2014
DOI: 10.48550/arxiv.1410.6149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-unitarity or hidden observables?

Abstract: A free hermitian conformal field theory is considered in Minkowski, de Sitter and anti-de Sitter spacetimes. The first part of the paper studies spacetime inversion and conformal inversion, wherein their role in the field quantization is elucidated in those spaces. The second part of the paper is concerned with the non-unitary evolution of detector's state. Several examples of such processes are provided with a clarification of how the unitarity is preserved with still having well-known thermal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…The non-conformally flat case is also an important issue [36,51]. The method established in the present paper can also be applied to such cases, which will be discussed further later.…”
Section: Discussionmentioning
confidence: 93%
“…The non-conformally flat case is also an important issue [36,51]. The method established in the present paper can also be applied to such cases, which will be discussed further later.…”
Section: Discussionmentioning
confidence: 93%
“…The various aspects of non-unitary lepton mixing are extensively discussed in the literature in both phenomenological and theoretical perspectives [30][31][32][33][34][35][36][37][38][39][40]. In [41], it has been shown that the neutrino factory experiment can provide an excellent probe for non-unitarity effects which are emerging in the minimal inverse seesaw model.…”
Section: Introductionmentioning
confidence: 99%